Knowledge, Attitudes, and Practices in Bungkulan Buleleng Village Communities Related to the Implementation of COVID-19 Vaccination - Yuliawati, Agustina Nila; Andika, Dewa Made Dwi (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2024)
Background: The contribution of the community through their knowledge, attitudes, and practices are essential to control COVID-19 through vaccination.Objectives: This study aims to analyze the relationship between knowledge, attitudes, and practices of the community related to implementing the COVID-19 vaccine.Methods: This observational study with a cross-sectional design was carried out from June to July 2023. Samples of 155 respondents were obtained through convenience sampling. Inclusion criteria include the community domiciled in Bungkulan Village, aged ≥18 years, and is willing to be involved in research, while respondents who didn’t fill in the complete questionnaire are excluded from research. Data was collected using self-developed offline questionnaire. The relationship of knowledge, attitudes, and practices was analyzed by multiple linier regression and Spearman-rho test (95% CI).Results: Findings showed that the majority of respondents were aged 25-29 years old (30.32%), male (76.13%), graduated from high school (65.16%), worked (89.68%), didn’t experience comorbidities (96.13%) and AESI (87.10%), lack of knowledge (53.29 ± 23.24) but has a good attitude (75.18 ± 11.55) and practices (84.06 ± 16.17) related to the implementation of the COVID-19 vaccination. There is a significant relationship between knowledge with attitudes (r = 0.352; p = <0.001) and attitudes with practices (r = 0.257; p = <0.001), also knowledge and attitudes simultaneously influence the practice of Covid-19 vaccination (p=<0.001).Conclusion: A person's attitudes and practices in a positive direction tend to begin with good knowledge. Strong sources of public health information and communication are necessary to develop good knowledge.